Perceptions and Motivations for Uterus Transplant in Transgender Women - Jones, Benjamin P. (JAMA Netw Open, 2021)
IMPORTANCE: Uterus transplant has been demonstrated to be a viable fertility-restoring treatment for women categorized as female at birth with absolute uterine factor infertility. Recent advancements, as well as considerations of fairness and equality in reproductive care, have now led to the possibility of uterus transplant being undertaken in transgender women. OBJECTIVE: To investigate the reproductive aspirations of transgender women and their perceptions of uterus transplant. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional survey study used a 27-item electronic questionnaire to investigate the reproductive aspirations of 182 transgender women older than 16 years, including their perceptions of and motivations for uterus transplant, between May 1 and November 1, 2019. MAIN OUTCOMES AND MEASURES: Perceptions of and motivations for uterus transplant, including perceived significance of the ability to gestate, menstruate, and have a physiologically functioning vagina. RESULTS: A total of 182 transgender women completed the questionnaire; most women (109 [60%]) were aged 20 to 29 years. Most did not have children prior to transitioning (167 [92%]) and expressed a desire to have children in the future (171 [94%]). In addition, most respondents agreed or strongly agreed that the ability to gestate and give birth to children (171 [94%]) and menstruate (161 [88%]) would enhance perceptions of their femininity. Similarly, high proportions strongly agreed or agreed that having a transplanted, functioning vagina would improve their sexual experience (163 [90%]), improve their quality of life (163 [90%]), and help them to feel like more of a woman (168 [92%]). Nearly all respondents (180 [99%]) believed that uterus transplant would lead to greater happiness in transgender women. More than three-quarters of the respondents (140 [77%]) strongly agreed or agreed that they would be more inclined to cryopreserve sperm if uterus transplant became a realistic option. CONCLUSIONS AND RELEVANCE: This study provides insights into the reproductive aspirations of transgender women and reports on their multifaceted motivation to undergo uterus transplant. The survey responses suggest that transgender women would choose to have female physiologic experiences, such as menstruation and gestation, as well as potentially having a physiologically functioning transplanted vagina. If proven feasible and safe in this setting, uterus transplant may facilitate the achievement of reproductive aspirations, improve quality of life, and further alleviate dysphoric symptoms in transgender women.